Peer review of the pesticide risk assessment of the active substance oxamyl. (18th May 2022) - ,; Alvarez, Fernando; Arena, Maria; Auteri, Domenica; Binaglia, Marco; Federica Castoldi, Anna; Chiusolo, Arianna; Colagiorgi, Angelo; Colas, Mathilde; Crivellente, Federica; De Lentdecker, Chloe; Egsmose, Mark; et al.
Abstract: The conclusions of the EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, Italy, and co‐rapporteur Member State, France, for the pesticide active substance oxamyl and the assessment of applications for maximum residue levels (MRLs) are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012, as amended by Commission Implementing Regulation (EU) No 2018/1659. The conclusions were reached on the basis of the evaluation of the representative uses of oxamyl as a nematicide on potato and tobacco (field use), on tomato (permanent greenhouse), on cucurbits (edible and inedible peel), pepper, aubergine and plants nurseries of the above‐mentioned crops on soil bed preparation (permanent greenhouse). The reliable end points, appropriate for use in regulatory risk assessment and the proposed MRLs, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.